IN VITRO ANTHELMINTIC ACTIVITY OF MAYTENUS EMARGINATA STEM BARK ON INDIAN ADULT EARTHWORM - JOSHI, UMESH PRABHAKAR; WAGH, RAJENDRA DAYARAM (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The development of anthelmintic activity and the high cost of synthetic anthelmintic drugs it leads to the evaluation of medicinal plants as an alternative source of anthelmintics. In the current study, in vitro experiments were conducted to determine the possible anthelmintic effects of crude methanolic, aqueous, and hydroalcoholic extracts of the stem bark of Maytenus emarginata on eggs and adult Pheretima posthuma and Ascaridia galli. Methods: Three concentrations (10, 25, and 50 mg/ml) of methanolic, aqueous, and hydroalcoholic extracts of plant M. emarginata were studied in activity which involved the determination of the time of paralysis (called as vermifuge) and time of death (called as vermicidal) of the worms. Piperazine citrate in same concentration as those of extract was included as standard reference and normal saline water with 1% carboxymethyl cellulose as control. Results: The methanolic, aqueous, and hydroalcoholic extracts exhibited significant anthelmintic activity at a concentration of 50 mg/ml. Peak activity was exhibited by the methanolic extract at a concentration of 50 mg/ml. Conclusion: The overall findings of the present study have shown that M. emarginata contain possible anthelmintic compounds and further evaluation of these plants should be carried out. The traditional use of anthelmintic activity of this plant is genuine.